Computer and communication engineering : first International Conference, ICCCE 2018, Guayaquil, Ecuador, October 25-27, 2018, Proceedings /: first International Conference, ICCCE 2018, Guayaquil, Ecuador, October 25-27, 2018, Proceedings. (2019) - Unknown
No abstract available